Analysis of pulsatile combined electroosmotic and shear-driven flow of generalized Maxwell fluids in a microchannel with slip-dependent zeta potential. (1st January 2023) - Mahanta, Kaushik; Panda, Swapnil; Banerjee, Debanjan; Pati, Sukumar; Biswas, Pankaj
Abstract: The present study investigates the flow characteristics for a pulsatile, combined electroosmotic and shear-driven flow of generalized Maxwell fluid through a straight planar microchannel including the effect of hydrodynamic slippage on asymmetric zeta potential. Mathematical expressions have been obtained in dimensionless form for the electrical potential distribution of the electrical double layer (EDL), velocity distribution and the volumetric flow rate after analytically solving the Poisson-Boltzmann and momentum equations. Critical values and critical ranges of time period of oscillating electric field have been obtained for no-slip and slip cases respectively where anomalous behaviour of dimensionless volumetric flow rate is observed. Flow rate magnitude sensitivity on hydrodynamic slippage is also analyzed. Moreover, critical values of the time period of oscillating electric field are obtained where the sensitivity of flow rate magnitude on the relaxation time of Maxwell fluid vanishes. Similarly, pivotal values of the time period of oscillating electric field are obtained at which the sensitivity of flow rate magnitude on the relaxation time of Maxwell fluid becomes invariant with the lower wall velocity.